Corrosion-resistant functional current collector, preparation method thereof, electrode plate and battery
By adding rare earth metal elements into the oxidation base layer of the functional current collector, forming a composite oxidation base layer and preparing a metal layer on its surface, the problem of insufficient hardness and corrosion resistance of the oxidation base layer is solved, and the performance of the functional current collector is significantly improved.
Patent Information
- Application Number
- CN202510026646.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2045-01-08
AI Technical Summary
The oxidation base layer in existing functional current collectors has low hardness and corrosion resistance, and is prone to damage or corrosion during preparation and use, resulting in reduced performance.
Rare earth metal elements, such as La, Eu, Sm, and Ce, are incorporated into the oxidation base layer of the functional current collector, to form a composite oxidation base layer, and a metal layer is prepared on its surface through magnetron sputtering or vacuum evaporation.
Improve the density, hardness, toughness, thermal strength and corrosion resistance of the oxidized base layer, reduce holes and membrane fold problems, and improve the stability of the functional current collector in the electrolyte.
Smart Images

Figure BDA0005232918180000071 
Figure BDA0005232918180000081
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a corrosion-resistant functional current collector and a preparation method thereof, an electrode sheet and a battery. Background Art
[0002] The functional current collector has a "sandwich" structure consisting of an inner polymer layer, an outer oxide primer layer, and a metal layer. The polymer layer is generally made of a polymer material such as PET, PP, or PI. The oxide primer layer, such as aluminum oxide, is attached to the polymer layer, and a metal layer, such as aluminum, is attached to the outer oxide primer layer.
[0003] The oxidation base layer improves the interfacial bonding strength between the polymer layer and the metal layer through mechanical interlocking and chemical bonding. In addition, when studying the bonding effect of polymer materials on the metal layer and the amorphous oxide surface through orbital quantized dynamics theory, it was found that the introduction of the metal oxide layer causes the carbonyl oxygen in the film substrate to form O-metal strong ionic bonds with the metal atoms in the metal oxide, such as O-Al. Similarly, during the deposition process, silicon oxide will also form chemical bonds with the oxygen-containing functional groups on the surface of the polymer material, thereby improving the interfacial bonding strength.
[0004] While the bonding between the metal layer and the polymer film can be improved by providing an oxide base layer, its thin thickness of only about 1 nm results in low hardness and corrosion resistance. This makes it susceptible to damage during metal layer preparation, such as melt-through by splashed metal or other impurities during the vapor deposition process, or corrosion from electrolyte penetration during battery use. Furthermore, while oxide base layers such as alumina ceramics offer high hardness, mechanical strength, and good chemical stability, they also suffer from high sintering temperatures and prone to grain growth, leading to performance degradation. Summary of the Invention
[0005] The purpose of the present invention is to provide a corrosion-resistant functional current collector and a preparation method thereof, an electrode sheet and a battery, so as to improve the performance of the composite current collector.
[0006] To achieve the above object, the technical solution provided by the present invention is:
[0007] The first aspect of the present application provides a corrosion-resistant functional current collector, comprising a polymer layer, an oxidized base layer and a metal layer; an oxidized base layer is attached to the polymer layer, and the outer side of the oxidized base layer is a metal layer, characterized in that: the oxidized base layer contains rare earth metal elements.
[0008] The rare earth metal element is selected from at least one of La, Eu, Sm and Ce; and the oxidation base layer is an alumina ceramic material base layer.
[0009] The second aspect of the present application provides a method for preparing a corrosion-resistant functional current collector, comprising the following steps: preparing an oxidized base layer on the surface of a high molecular polymer layer, adding rare earth metal elements when preparing the oxidized base layer to form a composite oxidized base layer containing rare earth metal elements, and preparing a metal layer on the surface of the composite oxidized base layer containing rare earth metal elements.
[0010] To optimize the above technical solutions, specific measures taken also include:
[0011] The oxidation base layer and the metal layer are respectively prepared by at least one of physical vapor deposition, chemical vapor deposition, in-situ forming or coating.
[0012] A composite oxide base layer containing rare earth metal elements is prepared on the surface of a high molecular polymer layer by magnetron sputtering technology. The target materials used in magnetron sputtering are rare earth oxide target and base metal oxide target. The magnetron sputtering process is carried out under a protective atmosphere.
[0013] Furthermore, the ratio of rare earth oxide target to base metal oxide target is 1-4:16-20; the power density of magnetron sputtering is 40-55W / cm 2 .
[0014] Furthermore, the rare earth oxide target is at least one of La2O3, Eu2O3, Sm2O3 and CeO2; and the base metal oxide target is an alumina target.
[0015] Furthermore, a metal layer is prepared on the surface of the composite oxidation base layer containing rare earth metal elements by vacuum evaporation.
[0016] The third aspect of the present application provides an electrode sheet comprising a corrosion-resistant functional current collector prepared by the method provided in the first aspect of the present application or the method provided in the second aspect of the present application.
[0017] The fourth aspect of the present application provides a battery comprising the electrode sheet provided in the third aspect of the present application.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] The present invention adds rare earth metal elements to the oxidized base layer of the functional current collector to improve the oxide lattice arrangement of the oxidized base layer, and improve the density, hardness, toughness, heat resistance and corrosion resistance of the oxidized base layer, thereby reducing the holes caused by the functional current collector being melted through by splashed metal liquid or splashed through by other impurities, as well as the problems of membrane wrinkling and thermal shrinkage during winding and unwinding. In addition, the increase in density and corrosion resistance can improve the problem of the functional current collector's polymer layer being easily corroded in the electrolyte, thereby achieving the purpose of optimizing the performance of the functional current collector.
[0020] As an additive, rare earth metals can be compounded with oxides in the oxide base layer to optimize the microstructure of the oxide base layer and improve the mechanical properties of the oxide base layer, especially for the base layer of alumina ceramic materials. Research has shown that doping with the rare earth material La2O can significantly increase the hardness of alumina ceramic materials, and Eu2O3 can increase the volume density and mechanical properties of alumina ceramic materials. Doping with the rare earth material Sm2O3 can greatly increase the relative density, flexural strength and fracture toughness of alumina ceramic materials. Doping with the rare earth material CeO2 can significantly improve the strength of alumina ceramic materials. By combining different rare earth materials, different optimization effects can be achieved, and their advantages complement each other to form a solution with an effect of 1+1 greater than 2.
[0021] When preparing a metal layer on the surface of a composite oxidation base layer containing rare earth metal elements, the present invention preferably prepares the metal layer by vacuum evaporation. The vacuum evaporation process can form a solid solution between the rare earth metal and the oxide in the oxidation base layer, thereby activating the crystal lattice and further improving the performance of the oxidation base layer. DETAILED DESCRIPTION
[0022] The above contents of the present invention are further described in detail below in the form of embodiments, but this should not be understood as the scope of the above subject matter of the present invention being limited to the following embodiments. All technologies implemented based on the above contents of the present invention fall within the scope of the present invention.
[0023] The test methods used in the following examples are conventional methods unless otherwise specified, and the reagents, methods and equipment used are conventional reagents, methods and equipment in the art unless otherwise specified.
[0024] For the sake of simplicity, this document only specifically discloses some numerical values and optional ranges. However, any lower limit can be combined with any upper limit to form an unspecified range; and any lower limit can be combined with other lower limits to form an unspecified range. Similarly, any upper limit can be combined with any other upper limit to form an unspecified range; the optional items in the optional range can also be combined arbitrarily.
[0025] Unless otherwise specified, the terms used in this application have the commonly known meanings commonly understood by those skilled in the art. Unless otherwise specified, the numerical values of the various parameters mentioned in this application can be measured using various measurement methods commonly used in the art.
[0026] The present invention provides a corrosion-resistant functional current collector, comprising a polymer layer, an oxidized primer layer and a metal layer; the polymer layer is adhered with an oxidized primer layer, and the outer side of the oxidized primer layer is a metal layer, characterized in that the oxidized primer layer contains rare earth metal elements.
[0027] In some embodiments, the rare earth metal element is selected from at least one of La, Eu, Sm, and Ce.
[0028] In some preferred embodiments, the oxide primer layer is an aluminum oxide ceramic material primer layer.
[0029] The present invention also provides a method for preparing a corrosion-resistant functional current collector, comprising the following steps: preparing an oxidized base layer on the surface of a high molecular polymer layer, adding rare earth metal elements when preparing the oxidized base layer to form a composite oxidized base layer containing rare earth metal elements, and preparing a metal layer on the surface of the composite oxidized base layer containing rare earth metal elements.
[0030] The present application adds rare earth metal elements to the oxide coating layer of the functional current collector to improve the oxide lattice arrangement of the oxide coating layer, and improve the density, hardness, toughness, heat resistance and corrosion resistance of the oxide coating layer, thereby reducing the holes caused by the functional current collector being melted through by splashed metal liquid or splashed through by other impurities, as well as the problems of membrane surface wrinkling and thermal shrinkage during winding and unwinding. In addition, the increase in density and corrosion resistance can improve the problem of the functional current collector's polymer layer being easily corroded in the electrolyte.
[0031] Non-limiting examples of the polymer material substrate of the present application may include one or more of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE) and the like.
[0032] The oxide base layer and metal layer of the present application are each prepared by at least one of physical vapor deposition, chemical vapor deposition, in-situ forming, or coating. Among these, physical vapor deposition is preferably vacuum evaporation and magnetron sputtering; chemical vapor deposition is preferably atmospheric pressure chemical vapor deposition and plasma-enhanced chemical vapor deposition; in-situ forming is preferably a method of forming a metal oxide passivation layer in situ on the surface of the metal layer; and coating is preferably die coating, blade coating, or extrusion coating.
[0033] In some preferred embodiments, a composite oxide base layer containing rare earth metal elements is prepared on the surface of the polymer layer by magnetron sputtering technology. The targets used in magnetron sputtering are rare earth oxide targets and base metal oxide targets. The magnetron sputtering process is carried out under a protective atmosphere.
[0034] Non-limiting examples of the protective atmosphere in this application may use helium, argon, or a noble gas.
[0035] In some embodiments, the ratio of rare earth oxide target to base metal oxide target is 1-4:16-20; the power density of magnetron sputtering is 40-55 W / cm 2 .
[0036] In some embodiments, the rare earth oxide target is at least one of La2O3, Eu2O3, Sm2O3 and CeO2; and the underlying metal oxide target is an alumina target.
[0037] The composite of rare earth metals and oxides in the oxide base layer can optimize the microstructure of the oxide base layer and improve the mechanical properties of the oxide base layer, especially for the base layer of alumina ceramic materials:
[0038] Experiments have shown that the present application can refine the grains, improve the microstructure, and inhibit the growth of alumina grains by adding rare earth metals to the base layer of alumina ceramic material, thereby improving the density of the alumina layer; by adding rare earth metals to the base layer of alumina ceramic material, the bridging, bending, and bifurcation of cracks in the alumina layer can be reduced, and the fracture energy can be increased, thereby increasing the mechanical strength, toughness and high-temperature mechanical properties; by adding rare earth metals to the base layer of alumina ceramic material, the hardness of the alumina layer can be increased, thereby improving the impact of holes caused by aluminum splashing, and at the same time reducing the residual stress caused by the film surface production and winding process.
[0039] Through experimental research on doping different rare earth materials, it was found that doping with rare earth material La2O can significantly improve the hardness of alumina ceramic materials, and Eu2O3 can improve the volume density and mechanical properties of alumina ceramic materials; volume density and mechanical properties; doping with rare earth material Sm2O3 can greatly improve the relative density, flexural strength and fracture toughness of alumina ceramic materials; doping with rare earth material CeO2 can significantly improve the strength of alumina ceramic materials.
[0040] In some preferred embodiments, the doped rare earth metal element is La2O3
[0041] In some preferred embodiments, a metal layer is formed on the surface of a composite oxide base layer containing a rare earth metal element by vacuum evaporation. The vacuum evaporation process allows the rare earth metal and the oxide in the oxide base layer to form a solid solution, thereby activating the crystal lattice and further optimizing the performance of the oxide base layer.
[0042] The present invention also provides an electrode sheet comprising the corrosion-resistant functional current collector of the present application.
[0043] The present invention also provides a battery comprising the electrode sheet of the present application.
[0044] In some embodiments, the batteries of the present application can be assembled into a battery module. The number of batteries contained in the battery module can be one or more. The specific number can be selected by those skilled in the art based on the application and capacity of the battery module.
[0045] In some embodiments, the battery modules described above may also be assembled into a battery pack. The battery pack may contain one or more battery modules, and the specific number may be selected by those skilled in the art based on the application and capacity of the battery pack.
[0046] The technical solution of the present invention is further described below through specific embodiments, wherein the selected base film is a PET film with a thickness of 6 to 8 μm, and a composite oxide base layer containing aluminum oxide and rare earth metals is plated on the base film by magnetron sputtering.
[0047] Example 1
[0048] In this embodiment, La2O3 is added to the oxide base layer by magnetron sputtering, and then aluminum is plated by vacuum evaporation. The specific operation is as follows:
[0049] The PET film was placed in a magnetron sputtering machine, and the target arrangement was set to 4 La2O3 targets plus 16 alumina targets (all with a purity of 99.95%). The magnetron sputtering power density was 50W / cm 2 , vacuum degree is 5*10 -4 Pa, the protective gas is argon, the flow rate is 50ml / min, and the oxide base layer thickness is about 1nm on both sides of the base film; then the film primed by magnetron sputtering is fixed to the winding trolley by vacuum evaporation, and the film is reeled in and out, and then the tension is adjusted, wherein the film-releasing end is at 120N and the reeling end is at 100N. After the winding trolley enters the evaporation chamber, it is vacuumed to 5*10 -3 Pa, open the winding trolley, control the speed at 280 ~ 300m / min, heat the evaporation boat and feed the aluminum wire at the same time, the wire feeding speed is 300 ~ 350mm / min, and the vacuum degree is controlled at 5*10 -2Pa; the heating temperature is 1000-1200℃, and 18 layers of aluminum are plated on both sides of the oxide base film surface in this way.
[0050] Example 2
[0051] In this embodiment, Sm2O3 is added to the oxide base layer by magnetron sputtering, and then aluminum is plated by vacuum evaporation. The specific operation is as follows:
[0052] The PET film was placed in a magnetron sputtering machine, and the target arrangement was set to 4 Sm2O3 targets plus 16 alumina targets (all with a purity of 99.95%). The magnetron sputtering power density was 50W / cm 2 , vacuum degree is 5*10 -4 Pa, the protective gas is argon, the flow rate is 50ml / min, and the oxide base layer thickness is about 1nm on both sides of the base film; then the film primed by magnetron sputtering is fixed to the winding trolley by vacuum evaporation, and the film is reeled in and out, and then the tension is adjusted, wherein the film-releasing end is at 120N and the reeling end is at 100N. After the winding trolley enters the evaporation chamber, it is vacuumed to 5*10 -3 Pa, open the winding trolley, control the speed at 280 ~ 300m / min, heat the evaporation boat and feed the aluminum wire at the same time, the wire feeding speed is 300 ~ 350mm / min, and the vacuum degree is controlled at 5*10 -2 Pa; the heating temperature is 1000-1200℃, and 18 layers of aluminum are plated on both sides of the oxide base film surface in this way.
[0053] Example 3
[0054] In this embodiment, CeO2 is added to the oxide base layer by magnetron sputtering, and then aluminum is plated by vacuum evaporation. The specific operation is as follows:
[0055] The PET film was placed in a magnetron sputtering machine, and the target arrangement was set to 4 CeO2 targets plus 16 alumina targets (all with a purity of 99.95%). The magnetron sputtering power density was 50W / cm 2 , vacuum degree is 5*10 -4 Pa, the protective gas is argon, the flow rate is 50ml / min, and the oxide base layer thickness is about 1nm on both sides of the base film; then the film primed by magnetron sputtering is fixed to the winding trolley by vacuum evaporation, and the film is reeled in and out, and then the tension is adjusted, wherein the film-releasing end is at 120N and the reeling end is at 100N. After the winding trolley enters the evaporation chamber, it is vacuumed to 5*10 -3 Pa, open the winding trolley, control the speed at 280 ~ 300m / min, heat the evaporation boat and feed the aluminum wire at the same time, the wire feeding speed is 300 ~ 350mm / min, and the vacuum degree is controlled at 5*10-2 Pa; the heating temperature is 1000-1200℃, and 18 layers of aluminum are plated on both sides of the oxide base film surface in this way.
[0056] Example 4
[0057] In this embodiment, La2O3 and Eu2O3 with a mass ratio of 1:1 are added to the oxide base layer by magnetron sputtering, and then aluminum is plated by vacuum evaporation. The specific operation is as follows:
[0058] The PET film was placed in a magnetron sputtering machine, and the target arrangement was set to 2 La2O3 and 2 Eu2O3 targets plus 16 alumina targets (all with a purity of 99.95%). The magnetron sputtering power density was 50W / cm 2 , vacuum degree is 5*10 -4 Pa, the protective gas is argon, the flow rate is 50ml / min, and the oxide base layer thickness is about 1nm on both sides of the base film; then the film primed by magnetron sputtering is fixed to the winding trolley by vacuum evaporation, and the film is reeled in and out, and then the tension is adjusted, wherein the film-releasing end is at 120N and the reeling end is at 100N. After the winding trolley enters the evaporation chamber, it is vacuumed to 5*10 -3 Pa, open the winding trolley, control the speed at 280 ~ 300m / min, heat the evaporation boat and feed the aluminum wire at the same time, the wire feeding speed is 300 ~ 350mm / min, and the vacuum degree is controlled at 5*10 -2 Pa; the heating temperature is 1000-1200℃, and 18 layers of aluminum are plated on both sides of the oxide base film surface in this way.
[0059] Example 5
[0060] This embodiment is substantially the same as the fourth embodiment, except that, after the oxide base layer is prepared by magnetron sputtering, aluminum is not plated by vacuum evaporation. Instead, aluminum is plated by magnetron sputtering. The specific operation is as follows:
[0061] The PET film was placed in a magnetron sputtering machine, and the target arrangement was set to 2 La2O3 and 2 Eu2O3 targets plus 16 alumina targets (all with a purity of 99.95%). The magnetron sputtering power density was 50W / cm 2 , vacuum degree is 5*10 -4 Pa, the protective gas is argon, the flow rate is 50ml / min, and the thickness of the oxide base layer formed on both sides of the base film is about 1nm; then the aluminum target is replaced, and the voltage of the target is set to 200V, with the film-unloading end at 120N and the winding end at 100N. After the winding trolley enters the evaporation chamber, it is vacuumed to 5*10 -3Pa, open the winding, the speed is 25m / min, the thickness of each sputtering aluminum is 20nm, and in this way, the front and back sides of the film are aluminum plated 5 times.
[0062] Comparative Example 1
[0063] In this comparative example, an oxidized base layer was prepared on the base film by magnetron sputtering, and then aluminum was plated by vacuum evaporation. The specific operation is as follows:
[0064] The PET film was placed in a magnetron sputtering machine, and the target material was set to 20 alumina targets (purity of 99.95%), and the magnetron sputtering power density was 50W / cm 2 , vacuum degree is 5*10 -4 Pa, the protective gas is argon, the flow rate is 50ml / min, and the oxide base layer thickness is about 1nm on both sides of the base film; then the film primed by magnetron sputtering is fixed to the winding trolley by vacuum evaporation, and the film is reeled in and out, and then the tension is adjusted, wherein the film-releasing end is at 120N and the reeling end is at 100N. After the winding trolley enters the evaporation chamber, it is vacuumed to 5*10 -3 Pa, open the winding trolley, control the speed at 280 ~ 300m / min, heat the evaporation boat and feed the aluminum wire at the same time, the wire feeding speed is 300 ~ 350mm / min, and the vacuum degree is controlled at 5*10 -2 Pa; the heating temperature is 1000-1200℃, and 18 layers of aluminum are plated on both sides of the oxide base film surface in this way.
[0065] Comparative Example 2
[0066] This comparative example is substantially the same as comparative example 1, except that, after the oxide base layer is prepared by magnetron sputtering, aluminum is not plated by vacuum evaporation, but by magnetron sputtering. The specific operation is as follows:
[0067] The PET film was placed in a magnetron sputtering machine, and the target material was set to 20 alumina targets (purity of 99.95%), and the magnetron sputtering power density was 50W / cm 2 , vacuum degree is 5*10 -4 Pa, the protective gas is argon, the flow rate is 50ml / min, and the thickness of the oxide base layer formed on both sides of the base film is about 1nm; then the aluminum target is replaced, and the voltage of the target is set to 200V, with the film-unloading end at 120N and the winding end at 100N. After the winding trolley enters the evaporation chamber, it is vacuumed to 5*10 -3 Pa, open the winding, the speed is 25m / min, the thickness of each sputtering aluminum is 20nm, and in this way, the front and back sides of the film are aluminum plated 5 times.
[0068] Experimental testing:
[0069] 1. Experimental test construction method
[0070] The functional current collectors prepared in the above examples and comparative examples were tested for tensile properties and surface pinhole-related properties.
[0071] (1) Tensile properties test
[0072] The room temperature tensile strength of the functional current collector is tested using an electronic universal material testing machine. The test conditions are: gauge length 10 mm, tensile speed 100 mm / min, width 15 mm. Other requirements are measured according to the method specified in GB / T 1040.3-2006.
[0073] (2) Surface pinhole test
[0074] The number of pinholes on the surface of the functional fluid collector is tested using a CCD machine. Through backlight imaging, a CCD linear array camera installed on the production line is used for real-time synchronous scanning to capture light leakage points and calculate the number of holes.
[0075] (3) Thermal deformation test
[0076] The functional current collector was sampled, each sample was 5*10cm in size, placed at different temperatures for 30min, and a force of 10N was applied. The length change in the MD (longitudinal) direction was measured using a caliper. The thermal elongation was calculated by comparing the length before the test. The formula is: Thermal elongation = (L1 形变后 -L1 形变前 ) / L1 形变前 .
[0077] 2. Test results
[0078] The results of the tests on tensile properties, surface pinholes, residual stress and other related properties of the functional current collectors prepared in the above examples and comparative examples are shown in Table 1, and the results of the thermal deformation tests are shown in Table 2.
[0079] Table 1 Tensile strength, surface pinhole data and residual stress of functional current collectors in Examples and Comparative Examples
[0080]
[0081]
[0082] Table 2 Thermal deformation data of functional current collectors in Examples and Comparative Examples (applied 10N force)
[0083] Group 180℃ 200℃ 220℃ 240℃ Example 1 0 0 0.41% 0.61% Example 2 0 0 0.35% 0.53% Example 3 0 0 0.31% 0.46% Example 4 0 0 0.22% 0.34% Example 5 0 0 1.65% 3.21% Comparative Example 1 2.78% 5.53% 6.12% 9.8% Comparative Example 2 3.03% 5.73% 6.87% 10.04%
[0084] It can be seen from Table 1 and Table 2 that the functional current collector provided by Examples 1 to 4 of the present invention, by adding rare earth oxides to the oxide base layer to form a composite oxide base layer, can refine the grains and improve the microstructure. At the same time, it can reduce the bridging, bending, and bifurcation of cracks in the aluminum oxide layer, thereby improving the fracture energy, thereby increasing the mechanical strength, toughness and high-temperature mechanical properties, improving the impact of holes caused by aluminum splashing, and reducing the residual stress caused by the film surface production and winding process.
[0085] Further in-depth research found that the effects of adding different rare earth oxides at the same time would be different. For Example 1, adding La2O3 can improve the hardness and density of the base layer, but when comparing it with Example 2 and Example 3, it was found that the increase in hardness of Example 1 can greatly reduce the number of holes, but the tensile strength is not as good as that of Example 2 and Example 3. A similar conclusion was also reached when comparing Example 2 and Example 3.
[0086] A comparative study of Example 4 with Examples 1-3 revealed that the addition of two rare earth oxides, namely, the doped rare earth material La2O, can significantly improve the hardness of the aluminum oxide layer, and Eu2O3 can improve the volume density and mechanical properties of the aluminum oxide layer, thereby improving the density and hardness of the base layer while ensuring mechanical strength and high-temperature mechanical properties. Therefore, a more preferred solution can be formed by selecting and combining different rare earth materials, whose advantages complement each other, forming a solution with an effect of 1+1 greater than 2.
[0087] Example 5 uses magnetron sputtering to perform aluminum plating, and the tensile strength, number of holes and residual stress are all worse than those of the vacuum evaporation method in Examples 1-4. This is mainly because the metal layer is prepared on the surface of the composite oxidation base layer of rare earth metal elements. The vacuum evaporation process can form a solid solution between the rare earth metal and the oxide in the oxidation base layer, thereby activating the lattice and further improving the performance of the oxidation base layer.
[0088] Comparative Examples 1 and 2 used pristine alumina as the base coat and were then aluminum-plated using different methods. Compared to the base coat doped with rare earth metals, the tensile strength, number of holes, and residual stress were significantly worse. When the base coat did not contain rare earth metals, as in Comparative Examples 1 and 2, the results of aluminum plating using vacuum evaporation or magnetron sputtering were similar. Furthermore, vacuum aluminum plating carries the risk of aluminum splashing, which can result in more surface pinholes and reduced tensile strength.
[0089] The above description is only a preferred embodiment of the present invention and does not constitute any form of limitation to the present invention. Any simple modification, equivalent replacement and improvement made by any technician familiar with the profession to the above embodiment without departing from the scope of the technical solution of the present invention and based on the technical essence of the present invention shall still fall within the scope of protection of the technical solution of the present invention.
Claims
1. A corrosion-resistant functional current collector, comprising a polymer layer, an oxidized primer layer and a metal layer; the polymer layer is attached with an oxidized primer layer, and the outer side of the oxidized primer layer is a metal layer, characterized in that: The oxidized primer layer contains rare earth metal elements.
2. The corrosion-resistant functional current collector according to claim 1, characterized in that: The rare earth metal element is selected from at least one of La, Eu, Sm and Ce; the oxide base layer is an alumina ceramic material base layer.
3. A method for preparing a corrosion-resistant functional current collector, characterized in that: The method comprises the following steps: preparing an oxidized primer layer on the surface of a high molecular polymer layer, adding rare earth metal elements when preparing the oxidized primer layer to form a composite oxidized primer layer containing rare earth metal elements, and preparing a metal layer on the surface of the composite oxidized primer layer containing rare earth metal elements.
4. The method for preparing the corrosion-resistant functional current collector according to claim 3, characterized in that: The oxidation base layer and the metal layer are prepared by at least one of physical vapor deposition, chemical vapor deposition, in-situ forming or coating.
5. The method for preparing the corrosion-resistant functional current collector according to claim 3, characterized in that: A composite oxide base layer containing rare earth metal elements is prepared on the surface of a high molecular polymer layer by magnetron sputtering technology. The target materials used in magnetron sputtering are rare earth oxide target materials and base metal oxide target materials. The magnetron sputtering process is carried out under a protective atmosphere.
6. The method for preparing the corrosion-resistant functional current collector according to claim 5, characterized in that: The ratio of rare earth oxide target to base metal oxide target is 1-4:16-20; the power density of magnetron sputtering is 40-55W / cm 2 .
7. The method for preparing the corrosion-resistant functional current collector according to claim 5, characterized in that: The rare earth oxide target material is at least one of La2O3, Eu2O3, Sm2O3 and CeO2; the base metal oxide target material is an aluminum oxide target material.
8. The method for preparing the corrosion-resistant functional current collector according to claim 3, characterized in that: A metal layer is prepared on the surface of a composite oxidation base layer containing rare earth metal elements by vacuum evaporation.
9. An electrode sheet, characterized in that: A corrosion-resistant functional current collector prepared by the method described in claim 1 or 2 or any one of claims 3-8.
10. A battery, characterized in that: The electrode sheet comprising claim 9.
Citation Information
Patent Citations
Aluminum oxide ceramic coating with nano crystal structure and preparation method thereof
CN102409280A
Shell and manufacturing method for shell
CN102534611A
Preparation method of honeycomb ceramic net through Lu and N co-doped TiO2 photocatalysis
CN103406136A
Preparation method of anti-corrosion die-casting aluminum alloy containing europium and lanthanum
CN108048706A
System and method for preparing composite material with oxide intermediate layer
CN112144018A
Cited By
Functional current collector with optimized base layer, preparation method of functional current collector, pole piece and battery
CN120581602A